Catch-up immunisation for migrant children in Melbourne: A qualitative study with providers to determine key challenges. Issue 47 (8th November 2022) - Overmars, Isabella; Kaufman, Jessica; Holland, Philippa; Danchin, Margie; Tuckerman, Jane
Highlights: Migrant family needs are not well considered in the Australian National Immunisation Program. System improvements are required to support service delivery to migrants. General practitioners had limited time, skills, and motivation for catch-ups. Resources and training are needed to support catch-up scheduling and reporting. Funding provider time to calculate the schedule could overcome most limitations. Abstract: Background: Current models of immunisation service delivery in Australia are not meeting the needs of migrant children, who experience a higher burden of vaccine preventable disease and lower immunisation rates compared to non-migrant children. Understanding the experiences of immunisation providers is critical for designing effective and tailored interventions to improve this service. This study aimed to identify the facilitators and barriers to providers delivering a comprehensive catch-up immunisation service to migrant children in Melbourne, Australia. Methods: Semi-structured interviews with council and general practice immunisation providers were conducted. Recorded interviews were transcribed and coded inductively using thematic analysis. Identified themes were then deductively categorised according to the Capability, Opportunity and Motivation of Behaviour (COM-B) model. Results: Twenty-four providers (five practice nurses, six general practitioners, six council nurses and seven council administration officers) were interviewed between March and June 2021. Fourteen themes were identified that contributed to the delivery of an effective catch-up immunisation service. Capability themes included training, experience and skills to perform the service and communicate with families. Opportunity themes incorporated time, workplace norms, traits of migrant families, costs, systems and resources. Themes related to motivation were provider responsibility, beliefs about migrant health, and immunisation prioritisation. Conclusions: Key barriers for providers to deliver a comprehensive catch-up immunisation service were related to opportunity. Developing an online tool to support catch-up schedule development and reporting, and funding provider time to calculate the schedule are primary actions that could overcome opportunity barriers. Capability and motivation barriers for general practitioners included limited time, skills, and motivation compared to nurses. These barriers may be overcome with improvements to training that focus on upskilling nurses to deliver the catch-up service. Service delivery challenges are multifactorial, requiring a range of strategies to optimise this service and increase immunisation coverage in migrant children.